2019
DOI: 10.1111/mmi.14235
|View full text |Cite
|
Sign up to set email alerts
|

The plasmid‐borne quinolone resistance protein QnrB, a novel DnaA‐binding protein, increases the bacterial mutation rate by triggering DNA replication stress

Abstract: Summary Bacterial antibiotic resistance, a global health threat, is caused by plasmid transfer or genetic mutations. Quinolones are important antibiotics, partially because they are fully synthetic and resistance genes are unlikely to exist in nature; nonetheless, quinolone resistance proteins have been identified. The mechanism by which plasmid‐borne quinolone resistance proteins promotes the selection of quinolone‐resistant mutants is unclear. Here, we show that QnrB increases the bacterial mutation rate. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 81 publications
(112 reference statements)
0
16
0
Order By: Relevance
“…Models were proposed in which PRPs bind to the positively charged GyrA dimer ( 19 , 22 ). In more recent pull-down experiment ( 48 ), GST-tagged QnrB1 protein was shown to bind E. coli GyrB stronger than GyrA. Likewise, in two-hybrid system experiments the QnrB1 interaction signal for GyrB was 7- to 11-fold higher than the signal for GyrA ( 49 ).…”
Section: Discussionmentioning
confidence: 97%
“…Models were proposed in which PRPs bind to the positively charged GyrA dimer ( 19 , 22 ). In more recent pull-down experiment ( 48 ), GST-tagged QnrB1 protein was shown to bind E. coli GyrB stronger than GyrA. Likewise, in two-hybrid system experiments the QnrB1 interaction signal for GyrB was 7- to 11-fold higher than the signal for GyrA ( 49 ).…”
Section: Discussionmentioning
confidence: 97%
“…Nonetheless, a study published in 2019 showed that qnrB has a general mutator effect in both the presence and the absence of ciprofloxacin and also showed that QnrB interacts with DnaA, subsequently regulating the formation of the DnaA-oriC complex and leading to the upregulation of genes near oriC. This results in DNA replication stress, which in turn favors both an increase in the number of plasmids, independently of Qnr-topoisomerase interactions, and higher mutation rates (255). In the last years, the effect of TMQR on the further selection of quinolone resistance mechanisms and bacterial survival in the presence of lethal concentrations of quinolones has been analyzed (256)(257)(258).…”
Section: Clinical Relevance Of Tmqrmentioning
confidence: 99%
“…In addition, it has also recently been shown that qnrB promotes DNA mutations and thereby fluoroquinolone-resistant mutants by triggering DNA replication stress. (Li et al, 2019) In this context, the SOS regulation of such PMQR genes have clinical implications, not only in term of infectious disease treatments, but also to prevent the dissemination of resistance genes. It has been clearly demonstrated that the qnrB-mediated quinolone resistance is induced upon exposure to sub-MICs of fluoroquinolone (Re et al, 2009).…”
Section: Discussionmentioning
confidence: 99%